PEMODELAN BASIS DATA AKADEMIK UNIVERSITAS XYZ MENGGUNAKAN PENDEKATAN OBJEK - Fera Tri Wulandari (Universitas Boyolali, 2019)
Academic database modeling use an object approach is made by looking at the problems of the system that correspond to real-world objects. Academic database design to connect between requirements specifications and implementation that will help the development of academic information systems and determine the quality of information produced. The design of the XYZ University academic database is done using database modeling using the object approach.The methodology carried out is directly using document collection and interviews with parties related to data processing related to academic data. After getting complete data about the object so that database design can be done. Designing is the first step after getting information to apply to the application.The series of activities carried out in object-oriented modeling includes analysis and design of academic databases. The formed database can be used as a reference for designing academic information systems so that the information produced is accurate, fast and relevant